SCondi: A Smart Context Distribution Framework Based on a Messaging Service for the Internet of Things - Jongmoon Park; Myung-Joon Lee (Journal of Applied Mathematics)
When developing IoT (Internet of Things) applications, context distribution is a key feature to support effective delivery of related contextual data obtained from things to all interested entities. With the advent of the IoT era, multiple billion devices can generate huge amounts of data that might be used in IoT applications. In this paper, we present a context distribution framework named SCondi utilizing the messaging service which supports MQTT—an OASIS standard IoT messaging protocol. SCondi provides the notion of context channel as a core feature to support efficient and reliable mechanism for distributing huge context information in the IoT environment. The context channel provides a pluggable filter mechanism that supports effective extraction, tailoring, authentication, and security of information.